Understanding new approaches to professional learning community practice and secondary school teacher motivation - Hareesol Khun-Inkeeree; Muhammad Dzahir Kasa; Fatimah Noor Rashidah Mohd Sofian; Wan Rosni Wan Yakob (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study was determining the link between professional learning community (PLC) practice and teacher motivation in secondary schools in the Jeli District, Malaysia. The cross-sectional research method was chosen, and the research instrument were the Professional Learning Community Assessment-Revised (PLCA-R) and the Assessment of Teacher Motivation Questionnaire (ATMQ). The sample were used 171 from a population of 306 individuals. The Statistical Package for Social Science (SPSS) version 26.0 was used to analyze the study data. The result demonstrated that instructors in remote regions are working hard to guarantee that the professional learning community program is beneficial to them while also increasing their teaching motivation. The study’s implications have demonstrated the importance of cultivating the practice of professional learning communities in schools. Thus, the school can make continuous improvements to improve student performance as well as be a catalyst to motivate teachers to work harder to improve the quality of teaching and learning.